Marginalizacja ugrupowań ekologicznych na scenach politycznych państw Europy Środkowo-Wschodniej w okresie transformacji ustrojowej - Łukaszewski, Marcin (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
In the period 2008–2011, twelve parliamentary elections were held in eight Central and East European states. Their results demonstrated the decreasing importance of green parties on the political stage in this part of Europe. The author of this paper tries to translate the concept developed by Allan Sikk and Rune Holmgaard Andersen, concerning the evolution of Estonian green parties, to party systems in CEE states. The paper also discusses the evolution of the status of green parties and their probable placement in party systems following the nearest parliamentary elections.